Theology of inclusivity and hospitality in the Evangelical Presbyterian Church in South Africa - Hundzukani P. Khosa-Nkatini (UIN Sunan Gunung Djati Bandung, 2023)
This article examines the liturgical practices of the Evangelical Presbyterian Church in South Africa (EPCSA), focusing on its Sunday liturgy, within the broader context of cultural and linguistic considerations. The EPCSA, formerly known as the Tsonga Presbyterian Church (TPC), has a diverse array of liturgies, each composed in Tsonga. Liturgy, as an integral part of worship, has evolved over the history of Christian practices, influenced by various cultures and people. This study emphasizes the cultural aspect of liturgy, asserting that the incorporation of nature into the relationship with God holds cultural significance. While the Tsonga language remains central to the EPCSA's tradition, the changing demographic landscape, with the church previously comprising Tsonga-speaking members exclusively, necessitates a reconsideration of its liturgical approach. The article utilizes a literature review to argue that the current Sunday liturgy may exhibit exclusivity. It underscores the importance of adapting liturgical practices to accommodate changes in the composition of the congregation, emphasizing the unity of diverse individuals coming together to worship a shared God despite their differences.